Engineering risk assessment with subset simulation - Au, Siu-Kui.; Wang, Yu, 1977- (Singapore : Wiley, 2014)
This book starts with the basic ideas in uncertainty propagation using Monte Carlo methods and the generation of random variables and stochastic processes for some common distributions encountered in engineering applications. It then introduces a class of powerful simulation techniques called Markov Chain Monte Carlo method (MCMC), an important machinery behind Subset Simulation that allows one to generate samples for investigating rare scenarios in a probabilistically consistent manner. The theory of Subset Simulation is then presented, addressing related practical issues encountered in th.
Includes bibliographical references and index.
Print version record.
Keywords: Engineering design -- Mathematics; Risk assessment -- Mathematics; Engineering design -- Mathematics; Risk assessment -- Mathematics; Set theory; Electronic books